A trust‐based mechanism in multipath routing using Biogeography‐Shun Optimization. (21st February 2021) - Govindaraj, Mahalakshmi; Arumugam, Suresh
Summary: In mobile ad hoc network, a group of mobile nodes interconnect with each other in an ad hoc manner without any centralized administration. Various applications are based on integrating mobile ad hoc network and cloud computing to enhance the processing and storing of mobile nodes. Cloud service providers provide mobile ad hoc network users access to applications and other mobile ad hoc network users. Implementing security mechanism for ad hoc routing can be a daunting task owing it its unique network traits. Blackhole attack found in the mobile ad hoc network takes place when malicious nodes attract data packets using a fresh destination route and drop the packets. In this work, a trust‐based routing that has a probability of a new packet forwarding is proposed to mitigate blackhole attacks. The ad hoc on‐demand multipath distance vector routing protocol is used in this work, which is based on the trust model that measures the trust of nodes and composes a decision, respectively. A novel optimization technique that has its basis in the Biogeography‐Shun Optimization algorithm is suggested for enhancing the multipath routing. Simulations demonstrate that the proposed method attains better performance by enhancing lifetime of network and packet delivery ratio and reducing end‐to‐end delay. Abstract : Implementing a security mechanism for a blackhole attack in mobile ad hoc network can be a daunting task owing it its unique network traits. In this work, a trust‐based routing that has a probability of a new packet forwarding is proposed to mitigate blackhole attacks. A novel optimization technique based on the Biogeography‐Shun Optimization algorithm is suggested for enhancing the multipath routing. Simulations demonstrate that the proposed method attains better security and network performance.